Leadership roles of grade school chairmen in the division of cavite city : an assessment - Ibanez, Lilia M. (Manila : National University, 1997)
This study is devoted to the leadership skills of the grade chairman in 10 dimensions. It describes the major skills important for leaders to understand the best way to exercise power with subordinates. The choice for a leader is not merely treating all subordinates exactly the same.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- List of tables -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.